Peningkatan Keterampilan Berpikir Kritis Siswa Kelas 3 SD Melalui Pembelajaran Matematika Dengan Pendekatan Deep Learning Dan Media Interaktif - Elvi Mailani; Nur Rarastika; Hizkia Adventy Saragih; Geby Juwita Patrisia Butar Butar; Olga Griselda Tarigan (GLOBAL SCIENTS PUBLISHER, 2025)
This article, deep learning-based mathematics learning combined with interactive media is discussed to improve students' critical thinking skills in grade III. A systematic literature review (SLR) approach was applied to twenty scientific articles published between 2020 and 2020. The results showed that implementing deep learning encourages students to actively participate in the process of solving contextual problems, think critically, and understand concepts thoroughly. The use of interactive media such as digital simulations and educational games encourage students to be more engaged in learning and improve their understanding of complex mathematical concepts. However, major issues such as infrastructure shortages and teachers' lack of technological capabilities hinder implementation. This study found that cross-stakeholder collaboration and adaptive education system support are necessary for the success of this approach.